Identification of the Need for PhET Simulation-based Interactive Media for Learning in Vocational High Schools - Endrayani, Iin; Efendi, Agus; Yamtinah, Sri (Journal of Education Reseach and Evaluation, 2022)
An effective learning process cannot be separated from various supporting factors, one of which is the use and support of technology during the learning process. Therefore, this research aims to identify the need for digital media in interactive media formats to support learning in vocational high schools. This research method is included in quantitative research with the type deskriptive, using non-test data collection techniques in the form of a questionnaire as the research instrument. The subjects of this research are vocational high school students majoring in electrical power installation engineering, totaling 36 students. The data analysis technique used is descriptive by converting student responses into percentages. From the research results, information was obtained that so far teachers are still comfortable with the lecture and discussion method, while in the context of using learning media, teachers still tend to consistently use printed modules and printed material books. The use of ICT tools by teachers is very minimal, even though almost 72.2% of students have been able to operate computers and are quite familiar with digital technologies. Through this research, information was also obtained that most students agree with the innovation of ICT-based learning media in the format interactive media to support learning which so far has very minimal application and integration of ICT. This research is expected to provide new insights regarding the importance of identifying what students need in order to improve the quality of education.